2014
DOI: 10.1007/s00264-014-2539-z
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic partial meniscectomy is superior to physical rehabilitation in the management of symptomatic unstable meniscal tears

Abstract: Pain and swelling improved after physical therapy. However, patients were not satisfied as limited range of knee motion persisted. APM was superior to physical therapy in treating symptomatic unstable meniscal tears, with high patient satisfaction and restored knee function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 23 publications
1
30
1
1
Order By: Relevance
“…The prevalence of nontraumatic meniscus lesions is 31% according to the Framingham study (9). Arthroscopic partial meniscectomy has been the first-line treatment for these injuries for a long time (3,4,(10)(11)(12) and positive clinical outcomes have been demonstrated for this procedure in several cohort studies (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of nontraumatic meniscus lesions is 31% according to the Framingham study (9). Arthroscopic partial meniscectomy has been the first-line treatment for these injuries for a long time (3,4,(10)(11)(12) and positive clinical outcomes have been demonstrated for this procedure in several cohort studies (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Since previous non-randomized studies have demonstrated benefits for a surgical treatment of meniscus lesions (10)(11)(12), we put forward the hypothesis that there is a subgroup of patients that benefit from surgery.…”
Section: Discussionmentioning
confidence: 99%
“…V intervenční skupině tedy došlo k zaznamenání výrazně menší bolestivosti v operovaném kloubu než u skupiny kontrolní. Nižších hodnot škály VAS u 71 pacientů po artroskopické operaci, menisektomii, dosahuje ve svém výzkumu Ghazaly [29]. Symptomatická léčba fyzikální terapií cílená na otok, bez navazující fyzioterapie, dosáhla průměrných hodnot před intervencí 7,4 a po osmi týdnech hodnoty 1,9.…”
Section: Diskuseunclassified
“…Symptomatic, unstable meniscus tears require excision to provide a stable meniscal rim. In 2015, El Ghazaly et al 7 published a prospective cohort identifying 70 patients with persistent symptomatic, unstable meniscus tears to evaluate the role of a regimented physical therapy program. Patients who met the inclusion criteria underwent physical therapy and were supervised and instructed by the same physiotherapist three times a week for 8 weeks.…”
Section: Arthroscopic Partial Meniscectomymentioning
confidence: 99%
“…[8][9][10] Some trials have concluded that there is limited benefit of APM in patients with advanced osteoarthritis, 8,9 while other evidence exists demonstrating some benefit in those with mild to moderate osteoarthritis. 7,10 Herrlin et al 11 first published a prospective, randomized study in 2007, with a subsequent 5-year follow-up study 12 in which 97 patients were randomized either to APM or a rigorous exercise program. Because of persistent symptoms, 28% of the patients in the exercise arm crossed over to APM by 14 months.…”
Section: Arthroscopic Partial Meniscectomy In the Setting Of Knee Artmentioning
confidence: 99%